Новый вид мермитид (Nematode, Mermithidae) — паразит слепня - Рубцов, И.А.; Бей-Биенко, И.Г. (Вестник зоологии, 1974)
A new species of Mermitidae - Paramermis hybomitrae sp. n. is described. It was found when dissecting the Hybomitra arpadi Szila dy female caught in the suburbs of Severo-Eniseisk of the Krasnoyarsk territory.